Service Quality and its Relationship with Customer Satisfaction and Loyalty in a Saudi Arabian Automobile Company (Global Journal of Management and Business Research, 2015)
The main aim of this study was to examine the relationship between service quality, customer satisfaction and customer loyalty in the context of aSaudi ArabianAutomobile Company (SAACO). Spearman correlation analysis indicated that all quality dimensions have significant positive effect on both customer satisfaction and customer loyalty. A questionnaire was personally distributed to 140 customers and 117 were returned. The study suggests that in order for the automobile companies to keep up with the competition, it is essential to conduct periodic quality assessments to proactively identify and fix any gaps between customers' expectations and actual perceived service quality. Continuous improvement in service quality is necessary to increase customer satisfaction, loyalty, retention, market share and profitability.